1969
DOI: 10.1128/jvi.3.5.525-527.1969
|View full text |Cite
|
Sign up to set email alerts
|

Complement-Fixation Test for Detection of Herpes-like Viruses in Cell Cultures of Burkitt's Lymphoma

Abstract: Although biopsies of Burkitt's tumors contained no detectable complement-fixing (CF) antigen or antigens, tumor cell lines contained CF antigen or antigens related to the presence of a herpes-like virus particle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
1

Year Published

1970
1970
1974
1974

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
3
7
1
Order By: Relevance
“…These particles are indistinguishable from those previously observed in CK infected with blood of chickens inoculated with JM strain or other strains of MD (1, 9). Very similar virus forms were observed associated with two other tumors, the Lucke frog tumor (7) and tissue cultures derived from Burkitt's lymphoma (6). As seen with the Lucke frog tumor, Burkitt's lymphoma, and herpes simplex virus (10), multiple virus-related particles were observed primarily in the nuclei of JM-infected cells (Fig.…”
supporting
confidence: 59%
“…These particles are indistinguishable from those previously observed in CK infected with blood of chickens inoculated with JM strain or other strains of MD (1, 9). Very similar virus forms were observed associated with two other tumors, the Lucke frog tumor (7) and tissue cultures derived from Burkitt's lymphoma (6). As seen with the Lucke frog tumor, Burkitt's lymphoma, and herpes simplex virus (10), multiple virus-related particles were observed primarily in the nuclei of JM-infected cells (Fig.…”
supporting
confidence: 59%
“…in BL extracts prepared from ten-fold lower concentrations of cells than those used here (McCormick et al, 1969).…”
Section: Nt=not Testedsupporting
confidence: 77%
“…These studies suggest a correlation between antigens detected by indirect IF procedures on fixed cells, surface antigens found on viable cells (8), and the presence of herpes-like virus particles. We have reported that Burkitt cell cultures react by CF with African sera only if the herpes-like virus is detectable by electron microscopy (9). This paper describes the reactivity of normal American sera with Burkitt cell lines and demonstrates that, in accord with our results with African sera, the CF antigen was found only in cell lines containing the herpes-like virus.…”
supporting
confidence: 83%